THE EFFECT OF FINANCIAL LITERACY, HUMAN RESOURCE COMPETENCE, AND E-COMMERCE IMPLEMENTATION ON THE FINANCIAL PERFORMANCE OF PALU CITY MSMES - Miswati, Miswati; Jurana, Jurana; Parwati, Ni Made Suwitri; Darmawan, I Putu Edi (Jurnal Manajemen Terapan dan Keuangan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, but in reality, they still face various problems, especially in efforts to improve their financial performance. This study was conducted to analyze the impact of financial management knowledge, workforce skills, and the use of e-commerce systems on the financial performance of MSMEs in Palu City. This study used a quantitative method with primary data sources collected through questionnaires distributed to 150 MSMEs. The sampling technique used purposive sampling, with the requirement that MSMEs have been operating for at least one year and have implemented e-commerce in their business operations. Data management included validity and reliability testing, descriptive data analysis, classical assumption analysis, multiple linear regression analysis, and hypothesis testing. The results showed that financial literacy, human resource competency, and e-commerce implementation have a positive and significant effect on the financial performance of MSMEs in Palu City. These findings indicate that strengthening these three aspects plays a crucial role in improving financial performance while supporting the sustainability of MSME businesses.